2016
DOI: 10.3390/su8121255
|View full text |Cite
|
Sign up to set email alerts
|

The Use of CFD in the Analysis of Wave Loadings Acting on Seawave Slot-Cone Generators

Abstract: Abstract:The reliability of Computational Fluid Dynamics (CFD) in reproducing qualitative and quantitative features of loadings exerted by waves on Seawave Slot-cone Generators (SSG) has been investigated via 17 numerical experiments, conducted with the suite Flow 3D. The geometry of the Wave Energy Converter (WEC), as well as the characteristics of the foreshore in front of it, were identical to those used by the authors in a laboratory study, carried out on a small scale model of a pilot plant to be located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Several CFD models of different wave power concepts have been developed and verified in recent years [2,3]. In [4], wave load of breaking waves on an overtopping device was studied in a physical wave flume, and in [5], the results were reproduced with good agreement using a RANS-VOF model. In [6,7] a point-absorbing WEC with linear-elastic mooring, moving in six degrees of freedom, was modeled showing good agreement with wave tank experiments, and in reference [8], another point-absorber device was modeled both fixed and freely floating.…”
Section: Introductionmentioning
confidence: 99%
“…Several CFD models of different wave power concepts have been developed and verified in recent years [2,3]. In [4], wave load of breaking waves on an overtopping device was studied in a physical wave flume, and in [5], the results were reproduced with good agreement using a RANS-VOF model. In [6,7] a point-absorbing WEC with linear-elastic mooring, moving in six degrees of freedom, was modeled showing good agreement with wave tank experiments, and in reference [8], another point-absorber device was modeled both fixed and freely floating.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, engineers design breakwaters to limit overtopping events, guaranteeing the tranquility of harbors. However, in some cases this phenomenon is instead favored and namely for wave energy converters which deploy the overtopping mechanism (Buccino et al, 2015a, 2015b, Contestabile et al, 2016 and in presence of wave attacks of particular severity. In the latter case, wave overtopping may reduce the magnitude of the wave action and, for vertical breakwaters, lower the probability of impulsive loadings (Goda 1995, Allsop et al, 1997, Calabrese and Buccino, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Buccino et al, 2016;Vicinanza et al, 2015, Dentale et al, 2014a, 8 sea-states were simulated, made up on 30 waves on average. The storms were driven by a very narrow banded spectrum, allowing to keep the wave period almost constant in each test.…”
Section: Introductionmentioning
confidence: 99%
“…Vicinanza et al and Buccino et al have made an interesting comparison between the CFD and laboratory experiments. [27,28] Recently, the integration of heaving-buoy WECs and floating breakwaters has become a topic of great research interest (Figure 1). Analytical studies on the hydrodynamic performance of the integrated WEC-breakwater were conducted and it was found that the peak efficiency can be achieved at 80% with a proper power take-off (PTO) [29,30].…”
mentioning
confidence: 99%